The virtues of variety in regional innovation systems and entrepreneurial ecosystems - Philip Cooke (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
Today, interesting and important interconnections have been made that promise great leaps forward for innovation systems and entrepreneurial ecosystems - especially operating at the regional or sub-national level of the space economy. Of course, there are politics in such relationships. Most notable are those that are critical of anything that 'interferes' with market hegemony (neoliberal bias) which has weakened commitments such as those pioneered in South Korea in the early years of the twenty-first century, later to be followed by numerous Scandinavian policy experiments (Denmark, Norway and Sweden) as well as austerity policy to enlarge regional governance spaces, as in Germany and France (not to mention the dismantling in 2010 of Anglo-regional governance in the UK). Meanwhile, however, it can be seen that good progress in regional innovation policy and entrepreneurial accomplishment at regional level proceeds apace. This is known as the "co-operative bias" in contemporary political economy. Entrepreneurial ecosystems and regional innovation systems are excellent examples of "generative growth" mechanisms (floated in Cooke, P, Generative Growth, Knowledge Economies and Sustainable Development: implications for Regional Foresight Policy, 2002) as a counter to Romer-style individualistic endogenous growth theory. The paper explores the virtues of variety against those of linearity in innovation and entrepreneurial ecosystems in exemplary empirical instances.
Keywords: 650